The Influence Of Brand Image, Promotion And Trust On Customer Loyalty At Bank BSI Nagoya Batam Branch - Rohmad; Yandra Rivaldo; Shandrya Victor Kamanda; Edi Yusman (Institute of Computer Science (IOCS), 2022)
Financial services certainly require good cooperation between banks and customers. The purpose of this study is to determine the influence of brand image, promotion and trust on customer loyalty. The population of this study is customers of Bank BSI Nagoya Batam Branch which amounts to 780 people. The sample consisted of 89 respondents, which were taken by the random sampling method. Data analysis used multiple regression and hypothesis testing and used SPSS version 23. The results of this study concluded that brand image variables have a significant effect on customer loyalty, promotion variables on customer loyalty, and trust variables on customer loyalty. Variables of brand image, promotion and trust simultaneously have a significant effect on customer loyalty